KEWENANGAN GUBERNUR SEBAGAI WAKIL PEMERINTAH PUSAT DALAM MELAKUKAN EVALUASI TERHADAP PERATURAN DAERAH KABUPATEN/KOTA TENTANG RENCANA TATA RUANG WILAYAH - Sundari, Siti; Sesung, Rusdianto (Jurnal HUKUM BISNIS, 2025)
The evaluation of the Regional Spatial Plan (RTRW) by the Governor aims to ensure that spatial policies at the district/city level are not only in accordance with local interests, but also support the national development agenda and maintain balance between regions. Compliance with national policies means that every policy taken by the regional government must be in line with the laws and regulations set by the central government. In its implementation, the evaluation process often faces several obstacles. Problems arise, there are differences in interpretation of regulations between the central and regional governments, and resistance from district/city governments who feel that their authority is being intervened. There is a conflict of interest between the central government, provincial government and district/city government in the preparation of the RTRW. In this case, the Governor must be able to balance the interests of the various parties in carrying out his evaluation duties. So it is necessary to emphasize a strong basis in terms of the limitations of the Governor's authority as a Representative of the Central Government in evaluating the Regency/City Regional Regulation on the Regional Spatial Plan, and it is necessary to know the legal consequences of the Regency/City Regional Regulation on the Regional Spatial Plan that are not in accordance with the results of the Governor's evaluation as a representative of the Central Government. Keywords: Authority of the Governor; Governor's Evaluation; Evaluation of the Regional Spatial Plan.